The entry ECG in the early diagnosis and prognostic stratification of patients with suspected acute myocardial infarction. - Yusuf, S; Pearson, M; Sterry, H; Parish, S; Ramsdale, D; Rossi, P; Sleight, P (1984)
475 patients with suspected uncomplicated myocardial infarction (MI) were divided into 3 groups based on their entry ECG: group 1--significant ST elevation; group 2a--ST depression or T inversion; group 2b--normal ECG. Infarction was confirmed in 99.7% of group 1, 68.5% of group 2a and 39.7% of group 2b patients. Despite similar clinical, haemodynamic and historical variables at presentation, group 1 patients had significantly larger MI, more in-hospital complications and a higher short-term and long-term mortality (P less than 0.005) than group 2 patients. The entry ECG of patients with suspected MI is an excellent and simple predictor of those who are most likely to have an MI confirmed and identifies a group of patients at high risk of death or developing complications.